Assessing the quality of care for paediatric depression and anxiety in Australia: A population-based sample survey. (October 2019) - Ellis, Louise A; Wiles, Louise K; Selig, Ruth; Churruca, Kate; Lingam, Raghu; Long, Janet C; Molloy, Charlotte J; Arnolda, Gaston; Ting, Hsuen P; Hibbert, Peter; Dowton, S Bruce; Braithwaite, Jeffrey
Objective: We examine the prevalence of quality care (as measured by adherence to recommendations in clinical practice guidelines) for Australian paediatric patients (⩽15 years) with depression and/or anxiety, using data from the CareTrack Kids study; a population-based study of the quality of healthcare practice in inpatient and ambulatory healthcare settings. Methods: A multistage stratified sample identified records of 6689 children. Of these, 156 records were identified for depression and 356 for anxiety. These were assessed for adherence to 15 depression and 13 anxiety indicators, respectively, using a review of medical records. Results: Adherence to assessment and management guidelines was low for both conditions: assessment bundle (depression = 33%, 95% confidence interval = [20, 48]; anxiety = 54%, 95% confidence interval = [43, 64] and depression management bundle = 35%, 95% confidence interval = [15, 60]). Across both conditions, the highest adherence was recorded for indicators that addressed prescription of medications (e.g. venlafaxine, 100%; benzodiazepines, 100%; selective serotonin reuptake inhibitor, 94% and antidepressants, 91%), while compliance was the lowest for ensuring children with depression had an emergency safety plan (44%), informing parents of the risks and benefits of prescribed anxiety medication (51%) and assessment for other causes (59% for depression; 68% for anxiety). Conclusion: These findings suggest that strategies are needed to improve guideline adherence for mental health disorders in children and adolescents, particularly among general practitioners. Learning from these indicators could inform clinical prompts in electronic medical records, as well as links to additional information, to assist in decision-making and streamline work practices.